Dynamic 3D MR Angiography of Intra- and Extracranial Vascular Malformations at 3T: A Technical Note - Ziyeh, S.; Strecker, R.; Berlis, A.; Weber, J.; Klisch, J.; Mader, I. (American Journal of Neuroradiology, 2005)
Summary: Time-resolved, contrast-enhanced 3D MR angiography combined with parallel imaging at 3T was applied to an intracranial arteriovenous malformation, a dural arteriovenous fistula, and an extracranial facial arteriovenous malformation. The temporal resolution was one image every 1.5 seconds. Arterial feeders were depicted in all three cases. Early venous drainage was observed in the intracerebral arteriovenous malformation and the dural arteriovenous fistula, but not in the facial arteriovenous malformation. All findings were concordant with conventional angiography.